1976
DOI: 10.1128/aac.10.6.893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clindamycin on Aminoglycoside Activity in a Murine Model of Invasive Escherichia coli Infection

Abstract: Previous studies have demonstrated that the early in vitro bactericidal activity of gentamicin and amikacin is inhibited by clindamycin. To investigate the possible clinical implications of these findings, the effect of clindamycin in combination with gentamicin or amikacin was compared with that of the aminoglycoside alone in the treatment of normal and neutropenic mice with Escherichia coli peritonitis and bacteremia. Mice treated with saline or clindamycin alone experienced rapid multiplication of bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Animal studies were performed by using a modification of a neutropenic mouse model previously reported from this laboratory (6). BALB/c mice (22 to 24 g) were made neutropenic with two intraperitoneal injections of 200 mg of cyclophosphamide per kg, separated by an interval of 54 to 56 h. This dosage schedule produced maximal granulocytopenia on day 4 after the first injection more consistently than did the single dose used in the earlier study.…”
mentioning
confidence: 99%
“…Animal studies were performed by using a modification of a neutropenic mouse model previously reported from this laboratory (6). BALB/c mice (22 to 24 g) were made neutropenic with two intraperitoneal injections of 200 mg of cyclophosphamide per kg, separated by an interval of 54 to 56 h. This dosage schedule produced maximal granulocytopenia on day 4 after the first injection more consistently than did the single dose used in the earlier study.…”
mentioning
confidence: 99%
“…Coverage is provided against most aerobic gram‐positive cocci and anaerobic bacteria including Staphylococcus, Bacteroides, Fusobacterium, Actinomyces , and Peptostreptococcus . Previous studies evaluating the combination of amikacin and clindamycin have conflicting results showing antagonism, no significant effect, or even synergism 22,23 . A study evaluating clindamycin and aminoglycosides against 50 strains of S. aureus found synergistic effects at 24 and 48 hours 24 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating the combination of amikacin and clindamycin have conflicting results showing antagonism, no significant effect, or even synergism. 22,23 A study evaluating clindamycin and aminoglycosides against 50 strains of S. aureus found synergistic effects at 24 and 48 hours. 24 An in vivo study in dogs comparing elution of antibiotics from AIPMMA found that pharmacologically, clindamycin was better at maintaining high concentrations in seroma fluid, granulation tissue and bone than cefazolin, ciprofloxacin, ticarcillin, tobramycin, or vancomycin.…”
Section: Discussionmentioning
confidence: 99%